Alterações morfofisiológicas e bioquímicas em sementes de mamona (Ricinus communis L.) submetidas à Radiação gama Cobalto60 - Lopes, Amanda Moreira (2012)
This study aimed to evaluate the radiosensitivity of castor bean seeds cultivar IAC80 subjected to different doses of cobalt60 gamma radiation. Firstly, the mechanical removal of the caruncle seeds was performed, after being pre-soaked for 24 hours and irradiated with cobalt60 gamma radiation (0, 50, 100, 150 and 200Gy) and, then, sown in polystyrene trays containing soil. Parameters such as electrical conductivity, emergence index and emergence rate, growth parameters and analysis of antioxidant enzymes (SOD, CAT and APX) measured/assessed in leaves and roots of castor bean plantlets /seedlings were evaluated. The results were submitted to ANOVA and the averages compared through Turkey test (5%). The electrical conductivity was not affected by the radiation doses used. The results showed that gamma radiation negatively affected plantlets/seedlings development, given that the dose of 200Gy significantly reduced emergence and speed of emergence index. The growth parameters showed a reduction in the plantlets size with the increase of radiation doses. The activities of antioxidant enzymes, superoxide dismutase showed a significant difference only at a dose of 200Gy to the leaves, not being significant to the roots. The activity of the enzyme ascorbate peroxidase showed increased activity in the leaves as the radiation doses were also increased. The activity of catalase showed no significant difference when exposed to different doses of gamma radiation in both leaves and roots. From the foregoing it can be concluded that the doses of Co60 gamma radiation used in this study were shown to have a negative effect on the morphological and physiological characteristics evaluated in this work. Regarding the activity of antioxidant enzymes (SOD and APX), the shoots of seedlings of castor bean was more sensitive to gamma radiation Co60 used.